2005
DOI: 10.1063/1.2136212
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of material mixing during local anodic oxidation nanolithography

Abstract: We investigate the chemical properties of nanostructures fabricated by local anodic oxidation (LAO) on epitaxial GaAs∕AlAs∕GaAs layers. We find evidence for the presence of Al compounds located in the topmost surface layers of the LAO structures. Our results cannot be explained within the framework of the commonly accepted mechanism that describes the growth of the LAO oxides in terms of diffusion of oxygen-rich ions through the growing oxide. A more general mechanism that explains our experimental findings is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Here, we found that the oxidation process mixes the original structure of the substrate, and the final state does not show any memory of the initial structure except for the average composition [11]. Moreover we observed that the interaction with photons leads to a decrease of the Ga oxide density and to an Al enrichment of the surface chemical composition.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Here, we found that the oxidation process mixes the original structure of the substrate, and the final state does not show any memory of the initial structure except for the average composition [11]. Moreover we observed that the interaction with photons leads to a decrease of the Ga oxide density and to an Al enrichment of the surface chemical composition.…”
Section: Introductionmentioning
confidence: 71%
“…We found evidence of the presence of Al compounds located in the topmost surface layers of all the LAO structures. We concluded that the LAO process involves not only the diffusion of the OH À ions inside the sample but also the diffusion of ionized substrate atoms and charged oxide complexes towards the sample surface [11].…”
Section: Resultsmentioning
confidence: 99%
“…The authors observed more or less strong surface reduction under irradiation with a micro-focused soft x-ray beam on SrTiO 2 , ZrO 2 , CeO 2 , and TiO 2 [68,69]. Experiments on oxide nanostructures obtained by local anodic oxidation (LAO) on GaAs and GaAs/AlAs/GaAs demonstrated that prolonged irradiation with soft x-rays (130 eV) can remove several layers of material, and eventually lead to the desorption of the whole LAO oxide [70][71][72][73][74].…”
Section: Oxide Surfaces and Interfacesmentioning
confidence: 99%
“…14 Intermixing of elements in a bilayer system of GaAs/AlAs has also been observed during LAO. 15 This is supposed to be due to the electric breakdown of thin semiconducting and dielectric films under anodic voltages greater than 10 V. 16 This process is very stochastic and is explained by different mechanisms and simulations. Dielectric breakdown is commonly studied for metal-insulator-metal configurations to measure dielectric strength.…”
mentioning
confidence: 99%